Hsp70 Suppresses Mitochondrial Reactive Oxygen Species and Preserves Pulmonary Microvascular Barrier Integrity Following Exposure to Bacterial Toxins - Li, Xueyi; Yu, Yanfang; Gorshkov, Boris; Haigh, Stephen; Bordan, Zsuzsanna; Weintraub, Daniel; Rudic, Radu Daniel; Chakraborty, Trinad; Barman, Scott A.; Verin, Alexander D.; Su, Yunchao; Lucas, Rudolf; et al. (Frontiers in Immunology, 2018)
Pneumonia is a leading cause of death in children and the elderly worldwide, accounting for 15% of all deaths of children under 5 years old. Streptococcus pneumoniae is a common and aggressive cause of pneumonia and can also contribute to meningitis and sepsis. Despite the widespread use of antibiotics, mortality rates for pneumonia remain unacceptably high in part due to the release of bacterial toxins. Pneumolysin (PLY), is a cholesterol-dependent toxin that is produced by Streptococcus and it is both necessary and sufficient for the development of the extensive pulmonary permeability edema that underlies acute lung injury (ALI). The mechanisms by which PLY disrupt the pulmonary endothelial barrier are not fully understood. Previously we found that reactive oxygen species (ROS) contribute to the barrier destructive effects of PLY and identified an unexpected but potent role of Hsp70 in suppressing ROS production. The ability of Hsp70 to influence PLY-induced barrier dysfunction is not yet described and the goal of the current study was to identify whether Hsp70 upregulation is an effective strategy to protect the lung microvascular endothelial barrier from G+ bacterial toxins. Overexpression of Hsp70 via adenovirus-mediated gene transfer attenuated PLY-stimulated increases in permeability in human lung microvascular endothelial cells (HLMVEC) with no evidence of cytotoxicity. To adopt a more translational approach, we employed a pharmacological approach using geranylgeranylacetone (GGA) to acutely upregulate endogenous Hsp70 expression. Following acute treatment (6h) with GGA, HLMVECs exposed to PLY displayed improved cell viability and enhanced endothelial barrier function as measured by both Electric Cell-substrate Impedance Sensing (ECIS) and transwell permeability assays compared to control treated cells. PLY promoted increased mitochondrial ROS, decreased mitochondrial oxygen consumption and increased caspase 3 cleavage and cell death, which were collectively improved in cells pre-treated with GGA. In mice, IP pre-treatment with GGA 24h prior to IT administration of PLY resulted in significantly less Evans Blue Dye extravasation compared to vehicle, indicating preserved endothelial barrier integrity and suggesting that the acute upregulation of Hsp70 may be an effective therapeutic approach in the treatment of lung injury associated with pneumonia.